Two-point boundary value problem for a partial differential equation in spaces of periodic functions - V.S. Ilkiv; Z.M. Nytrebych; P.Y. Pukach; M.I. Vovk (Математичні Студії, 2020)
We investigate the two-point in time boundary value problem for the partial differential equations of the second-order with one spatial variable and constant coefficients. The problem is considered in in the spaces of functions which Fourier coefficients are characterized by exponential behavior on the Cartesian product of the time interval and spatial domain $\mathbb{R}/2π\mathbb{Z}$.